Clot waveform analysis to differentiate mild, moderate, and severe hemophilia A - Timan, Ina Susianti; Chozie, Novie Amelia; Santoso, Novianti (Indonesian Pediatric Society, 2024)
Background Clot waveform analysis can be used to evaluate clot formation profiles. This waveform can be obtained from activated partial thromboplastin time (APTT) assays without additional reagents and shows different patterns in hemophilia patients with coagulation factor VIII (F VIII) deficiency or abnormality. Objective To determine the clot wave pattern and its process in clot formation phases (pre-coagulation, coagulation, and post-coagulation) in normal and hemophilia A subjects, analyze for possible correlations between clot wave parameters and F VIII activity, and obtain the pattern of coagulation curves in hemophilia subjects as a step to assess clot waveform analysis as a possible screening tool for hemophilia. Methods In this cross-sectional study, we performed clot wave analysis in 145 adult and pediatric subjects with hemophilia to obtain the clot wave pattern in this condition. Clot wave analysis was also done in 160 subjects with normal hemostasis to obtain reference clot wave parameters. Results In this study, the starting point of coagulation phase in normal subjects was between 30-40 seconds, with a shorter pre-coagulation phase and steeper slope. Hemophilia patients had a longer pre-coagulation phase and flatter slope, especially in severe hemophilia A patients, who had longer and more variable coagulation starting points (P<0.001). The absolute values of maximum coagulation velocity (Min1), maximum coagulation acceleration (Min2), and maximum coagulation deceleration (Max2) of hemophilia A patients were also lower than those of normal hemostasis patients, with lower absolute value seen in severe than in mild-moderate hemophilia A patients. A moderate correlation was found between Min1, Min2, and Max2 with F VIII activity (P<0.001). Conclusion Clot wave analysis may be considered as a method for screening hemophilia patients to distinguish mild-moderate and severe hemophilia A patients in health facilities that lack the ability to perform F VIII assays.